73.6k views
2 votes
Solve for the variable c in this equation:

a(c – b) = d

User SandyBr
by
5.8k points

2 Answers

3 votes

Final answer:

To solve for c in the equation a(c – b) = d, distribute a, add ab to both sides, and then divide by a to get c = (d + ab) / a.

Step-by-step explanation:

To solve for the variable c in the equation a(c – b) = d, follow these steps:

  1. Distribute the a across the parentheses by multiplying it with both c and –b, which gives us ac - ab = d.
  2. Add ab to both sides of the equation to isolate the term with c on one side, resulting in ac = d + ab.
  3. Finally, to solve for c, divide both sides of the equation by a, giving us c = (d + ab) / a.

By following these steps, you'll find the value of c in terms of a, b, and d.

User Ankit Jindal
by
5.6k points
2 votes

Answer:


(d)/(a) + b

Step-by-step explanation:

divide both sides by a

c - b =
(d)/(a) ( add b to both sides )

c =
(d)/(a) + b


User Manidos
by
5.8k points